2013
DOI: 10.1002/cmdc.201300096
|View full text |Cite
|
Sign up to set email alerts
|

The Lab Oddity Prevails: Discovery of Pan‐CDK Inhibitor (R)‐S‐Cyclopropyl‐S‐(4‐{[4‐{[(1R,2R)‐2‐hydroxy‐1‐methylpropyl]oxy}‐5‐(trifluoromethyl)pyrimidin‐2‐yl]amino}phenyl)sulfoximide (BAY 1000394) for the Treatment of Cancer

Abstract: Lead optimization of a high-throughput screening hit led to the rapid identification of aminopyrimidine ZK 304709, a multitargeted CDK and VEGF-R inhibitor that displayed a promising preclinical profile. Nevertheless, ZK 304709 failed in phase I studies due to dose-limited absorption and high inter-patient variability, which was attributed to limited aqueous solubility and off-target activity against carbonic anhydrases. Further lead optimization efforts to address the off-target activity profile finally resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(88 citation statements)
references
References 39 publications
0
86
1
Order By: Relevance
“…Lucking et al reported the original convergent synthetic route to roniciclib [103]. In this protocol, 1-fluoro-4-nitrobenzene (28) reacted with cyclopropanethiol to afford thioether 29 in 61% yield (Scheme 15).…”
Section: Roniciclib (Phase Ii)mentioning
confidence: 97%
See 2 more Smart Citations
“…Lucking et al reported the original convergent synthetic route to roniciclib [103]. In this protocol, 1-fluoro-4-nitrobenzene (28) reacted with cyclopropanethiol to afford thioether 29 in 61% yield (Scheme 15).…”
Section: Roniciclib (Phase Ii)mentioning
confidence: 97%
“…Roniciclib features an extremely rare chiral sulfoximine group and was developed from a CDK and vascular endothelial growth factor receptor (VEGF-R) inhibitor ZK 304709 [103,105] plagued by off-target inhibition against carbonic anhydrase (CA) and limited solubility in water; consequently it failed the phase I clinical trials. Since the sulfonamide group in ZK 304709 was most likely the reason for the toxicity, this function was replaced with a sulfoximine group, the line that eventually lead to the discovery of roniciclib.…”
Section: Roniciclib (Phase Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Examples of this interest are the pan--CDK inhibitor BAY 1000394 from Bayer, 3 and the ATR inhibitor AZD6738 from Astra--Zeneca 4 ( Figure 1), both developed for cancer therapy. Additional examples of biologically active molecules bearing the sulfoximine moiety are collected in Figure 1.…”
mentioning
confidence: 99%
“…In addition, we studied sulfoximine-based analogs of zolimidine [22], dapsone [23], and S0859 [24]. The most advanced examples stem from industry, where BayerPharma [25] and AstraZeneca [26] have promoted kinase inhibitors with sulfoximidoyl groups in their respective anticancer programs to clinical trials [27]. Switching from a sulfone to a sulfoximine allows retaining the drug effectiveness while improving the overall bioactivity profile by positively affecting solubility [28] and ADME properties [29].…”
Section: Introductionmentioning
confidence: 99%